2018
DOI: 10.1186/s12879-018-3391-3
|View full text |Cite
|
Sign up to set email alerts
|

Incubation period of typhoidal salmonellosis: a systematic review and meta-analysis of outbreaks and experimental studies occurring over the last century

Abstract: BackgroundSalmonella Typhi is a human pathogen that causes typhoid fever. It is a major cause of morbidity and mortality in developing countries and is responsible for several outbreaks in developed countries. Studying certain parameters of the pathogen, such as the incubation period, provides a better understanding of its pathophysiology and its characteristics within a population. Outbreak investigations and human experimental studies provide an avenue to study these relevant parameters.MethodsIn this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Another experimental study reported a shorter incubation period of a median of 6 days (IQR 5.1 to 7.8) in a control group with no vaccination who received a challenge dose of about 10 4 [49], similar to our initial value. In a systematic review conducted to estimate the distribution of incubation period and identify influencing factors [50], the mean incubation period between subgroups was reported to range from 9.7 to 21.2 days with previously vaccinated cases reporting longer incubation period. In an observational study of a large outbreak associated with Spanish spaghetti, the mean incubation period was 10.5 days with a median of 8 days [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another experimental study reported a shorter incubation period of a median of 6 days (IQR 5.1 to 7.8) in a control group with no vaccination who received a challenge dose of about 10 4 [49], similar to our initial value. In a systematic review conducted to estimate the distribution of incubation period and identify influencing factors [50], the mean incubation period between subgroups was reported to range from 9.7 to 21.2 days with previously vaccinated cases reporting longer incubation period. In an observational study of a large outbreak associated with Spanish spaghetti, the mean incubation period was 10.5 days with a median of 8 days [51].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of vaccination has not been considered in this model, vaccination has been reported to prolong the incubation period [50,55]. The effect of vaccination has been studied in an experimental study [49] where the time to microbiological diagnosis was similar in participants with and without vaccination; however, the median time to clinical diagnosis, which also represented the incubation period, was longer in the vaccine groups with reports of 8.5 and 10.4 days compared to the control group reporting 6.8 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rare cases, the incubation period can be as long as 3 weeks. 9 The patient said he had no diarrhea or constipation, which also makes typhoid fever less likely. Moreover, typhoid fever is more commonly associated with high unremitting fever, which is inconsistent with the patient's fever pattern.…”
Section: Wongmentioning
confidence: 99%
“…Cases of the disease among African children decrease, and increase in the acquisition of the antibody to start all complement-dependent killing of Salmonella, and subsequently, more effective blood phagocytes and opsoniza-tion (4)(5)(6). Measuring and detecting serum antibody markers in the clinical laboratory to evaluate a patient's health status is an important and valuable issue (6)(7)(8)(9)(10)(11). The affinity of an antibody to its antigen describes and characterizes the strength of the interaction between the antibody and the antigen and plays a critical role in the recovery of infection.…”
Section: Introductionmentioning
confidence: 99%